Goldmann applanation tonometry error relative to true intracameral intraocular pressure in vitro and in vivo. Issue 1 (December 2017) - McCafferty, Sean; Levine, Jason; Schwiegerling, Jim; Enikov, Eniko
Abstract Background Goldmann applanation tonometry (GAT) error relative to intracameral intraocular pressure (IOP) has not been examined comparatively in both human cadaver eyes and in live human eyes. Futhermore, correlations to biomechanical corneal properties and positional changes have not been examined directly to intracameral IOP and GAT IOP. Methods Intracameral IOP was measured via pressure transducer on fifty-eight (58) eyes undergoing cataract surgery and the IOP was modulated manometrically on each patient alternately to 10, 20, and 40 mmHg. IOP was measured using a Perkins tonometer in the supine position on 58 eyes and upright on a subset of 8 eyes. Twenty one (21) fresh human cadaver globes were Intracamerally IOP adjusted and measured via pressure transducer. Intracameral IOP ranged between 5 and 60 mmHg. IOP was measured in the upright position with a Goldmann Applanation Tonometer (GAT) and supine position with a Perkins tonometer. Central corneal thickness (CCT) was also measured. Results The Goldmann-type tonometer error measured on live human eyes was 5.2 +/−1.6 mmHg lower than intracameral IOP in the upright position and 7.9 +/− 2.3 mmHg lower in the supine position (p  < .05). CCT also indicated a sloped correlation to error (correlation coeff. = 0.18). Cadaver eye IOP measurements were 3.1+/−2.5 mmHg lower than intracameral IOP in the upright position and 5.4+/− 3.1 mmHg in the supine position (p  < .05). Conclusion Goldmann IOP measures significantly lower than true intracameral IOP by approximately 3 mmHg in vitro and 5 mmHg in vivo. The Goldmann IOP error is increased an additional 2.8 mmHg lower in the supine position. CCT appears to significantly affect the error by up to 4 mmHg over the sample size.